Аномальные каникулы: [фантастический роман] / Алексей Гравицкий, Сергей Палий - Гравицкий Алексей Андреевич (S.T.A.L.K.E.R., 2011)
Экземпляры: ф.8 (20240213) / Инвентарный номер: 64408 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Г 75 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-445